2015
DOI: 10.7314/apjcp.2015.16.2.451
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Breast Cancer in Relation to Reproductive Factors in North-west of Iran, 2013-2014

Abstract: More than one million new patients suffer from breast cancer annually in the world. In developed countries, breast cancer is the most common malignancy diagnosed among women, and in developing regions, it often ranks second to cervical cancer. This study aimed to investigate the relationship between incidence of breast cancer and reproductive factors in North-West of Iran. This retrospective analytical control-case study was conducted with 235 breast cancer patients and 235 women in the control group. Data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
(19 reference statements)
3
17
0
Order By: Relevance
“…While Age at menopause revealed in our study to have no association with breast diseases was consistent with a study done at north of Iraq which concluded that higher age at menopause was not a risk factor for postmenopausal breast cancer (Zangana & Garota, 2012). Otherwise a study conducted in Iran found that with increasing menopause age to over 50 years, odds of cancer incidence reached 50.1, and doubled at age over 60 years (Veisy, Lotfinejad, Salehi, & Zhian, 2015).…”
Section: Association Of Gynecological History and Obstetrical Historysupporting
confidence: 91%
“…While Age at menopause revealed in our study to have no association with breast diseases was consistent with a study done at north of Iraq which concluded that higher age at menopause was not a risk factor for postmenopausal breast cancer (Zangana & Garota, 2012). Otherwise a study conducted in Iran found that with increasing menopause age to over 50 years, odds of cancer incidence reached 50.1, and doubled at age over 60 years (Veisy, Lotfinejad, Salehi, & Zhian, 2015).…”
Section: Association Of Gynecological History and Obstetrical Historysupporting
confidence: 91%
“…Especially the mother affected by breast cancer is considerably more responsible about three times higher than other family members. Like different world wide studies (Shankar, 2015;Veisy, 2015) this study has been noticed that the factors "Menarche start early", "Menopause stop late" are another two significant factors for Breast cancer. From our analysis it is found that women whose menarche is started early have more high risk (OR=3.500) than late started women.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal menstruation time also implies from at front to increase or create breast cancer. Menarche starts early before 12 years and Menopause stops at late after 55 years are mostly responsible to increase breast cancer patients Shankar, 2015;Veisy, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to different epidemiologic studies in Iran, breast cancer is the first or second (after lung cancer) leading cause of death among cancerous women (Sadjadi et al, 2009;Kolahdoozan et al, 2010;Movahedi et al, 2012;Taghavi et al, 2012;Veisy et al, 2015) and the rate of death was increased from 3.933 to 4.92 per 100,000 cases between 2006 and 2010 (Enayatrad et al, 2015). Despite improvements in surgery and the use of adjuvant therapy, it continues to be fatal in many patients around the world.…”
Section: Introductionmentioning
confidence: 96%